ANALISIS HUBUNGAN POLA MENSTRUASI, STATUS GIZI, DAN KONSUMSI TABLET TAMBAH DARAH TERHADAP STATUS ANEMIA PADA REMAJA PUTRI DI DESA SIRNAGALIH, BOGOR - Rahayu Putri Nopitasari (2022)
Anemia is experienced by a third of all women of childbearing age (15-49 years) in the world. The increase incidence of anemia in women of childbearing age worldwide increased in 2015 by 28.5% to 29.3% in 2017. The increase in maternal mortality in Bogor Regency occurred in 2019 by 61.7% from the previous year in 2015 of 46.9% were mostly caused by bleeding and eclampsia. The purpose of this study was to examine the relationship between individual characteristics, menstrual patterns, nutritional status, and iron supplement intake on the anemia status of adolescent girls in Sirnagalih Village, Bogor. This research is included in a quantitative study with a cross-sectional research design which was carried out in Sirnagalih Village, Bogor on the period January-February 2022. The study population was all adolescent girls (10-19 years) in Sirnagalih Village, Bogor. The research sample was obtained using a purposive sampling technique of 78 respondents. Data analysis used primary data obtained using research instruments in the form of measuring height and weight, EasyTouch GcHb, and online questionnaires. The results of the bivariate analysis showed a significant relationship between iron supplement intake and the status of adolescent girls anemia in Sirnagalih Village, Bogor (p-value = 0.018 and POR = 0,128 (95% CI: 0,02-0,69)). The other variables did not have a significant relationship with the status of anemia in rheumatism in Sirnagalih Village, Bogor (p-value > 0.05).